Disability athletics - Schiffer, J. (New Studies in Athletics, 2015)
Disabled sports are sports played by persons with disabilities. As many disabled sports are based on existing able-bodied sports that have been modified to meet the needs of persons with a disability, they are sometimes referred to as adapted sports. However, not all disabled sports are adapted. Several sports specifically created for persons with a disability have no equivalent in able-bodied sports (e.g. Goalball for visually impaired athletes and wheelchair racing within athletics).